PENGARUH SPI TERHADAP KUALITAS INFORMASI LAPORAN KEUANGAN DENGAN KOMITMEN ORGANISASI DAN KOMPETENSI SDM SEBAGAI PEMODERASI (STUDI PADA SKPD PROVINSI BALI) - Nyoman Angga Pradipa; Budhananda Munidewi (Behavioral Accounting Journal, 2018)
The purpose of this study is to test the effect of internal control system to financial report quality with organization commitment dan human resources competence as moderating variabel. Using purposive sampling method to distribute the questionnaire, this study collect 42 data from financial department employee. The data were analyzed using Moderated Regression Analysis (MRA), and the results show that organization commitment and human resources competence was able to strenghten the relationship of internal control system and financial report quality.